Refugee Women with a History of Trauma: Gender Vulnerability in Relation to Post-Traumatic Stress Disorder. - Vallejo-Martín, Macarena; Sánchez Sancha, Ana; Canto-Ortiz, Jesús María (MDPI, 2021)
Refugees represent a population whose living conditions have a strong impact on their mental health. High rates of post-traumatic stress disorder (PTSD), more than other mental disorders, have been found in this group, with women having the highest incidence. The objective of the present systematic review was to identify and examine studies from the last fifteen years on the relationship between the impact of traumatic experiences and PTSD psychopathology in refugee women. Twelve studies were included, from which the overall results approved this relation. In addition, six of these studies show that exposure to sexual trauma in refugee women is associated with the high odds of being at risk for PTSD. These findings suggest that gender-related traumatic experiences can explain the high rate of PTSD in refugee women and highlight the unmet need for psychosocial health care in this population.
Keywords: Refugiadas; Estrés postraumático; Trauma psíquico; Crímenes contra las mujeres; Delitos sexuales; Refugee women; Post-traumatic stress disorder (PTSD); Traumatic experiences; Sexual violence; Systematic review